MET exon 14 skipping mutation positive non-small cell lung cancer: Response to systemic therapy. (April 2021) - Wong, Selina K.; Alex, Deepu; Bosdet, Ian; Hughesman, Curtis; Karsan, Aly; Yip, Stephen; Ho, Cheryl
Highlights: MET exon 14 skipping is a targetable driver alteration. The prevalence was 2.1 % in the British Columbia population. There was modest disease control with crizotinib, platinum-doublet and immunotherapy. Co-mutations with TP53 common. Abstract: Objectives: MET exon 14 skipping is a potentially targetable molecular alteration. The goals of this study were to identify patients treated in British Columbia with MET exon 14 skipping to understand prevalence, biology and response to treatment, and to identify molecular signatures that may predict for response or resistance to targeted MET therapy in the setting of advanced disease. Materials and Methods: A retrospective review was completed of patients found to have MET exon 14 skipping alterations between January 2016-September 2019. Information was collected on baseline characteristics, response to systemic treatments, and outcomes. Results: Out of 1934 advanced, non-squamous and never-smoking squamous NSCLC patients tested, 41 patients were found to have MET exon 14 skipping (2.1 %). MET alteration types: 2% CBL binding-domain mutations, 34 % poly-pyrimidine tract deletions, 63 % splice donor mutations or deletions. The most common co-mutation was TP53 (22 %). Thirty-three patients received systemic therapy. Physician-assessed disease control was 68 % among 19 evaluable patients treated with crizotinib, 80 % among 10 evaluable patients treated with platinum-based chemotherapy, and 70 % among 10 evaluable patients treated with immunotherapy. Median time to treatment discontinuation was 3.0, 2.8, and 2.4 months, respectively. Median overall survival for metastatic patients treated with any systemic therapy was 15.4 months. In this small cohort, there were no clear correlations between molecular aberrations and response, time to treatment discontinuation, or survival for crizotinib, chemotherapy, and immunotherapy. Conclusion: The prevalence of MET exon 14 skipping in a North American population was 2.1 %. Unlike other targetable mutations, patients were older and more commonly current or former smokers. Patients with MET exon 14 skipping alteration demonstrate disease control with crizotinib, platinum-based chemotherapy and immunotherapy. Co-mutations with TP53 were commonly noted, but correlation between co-mutations and efficacy of therapy were not identified in this cohort.